The crime of counterfeiting Package C diplomas and certificates of equivalency test results in the election for Keuchik Gampong Alue Ie Mirah East Aceh - Munawir, Munawir; Mandasari Saragih, Yasmirah (PT. Multidisciplinary Press Indonesia, 2024)
Forgery of Package C diplomas and certificates of equivalency exam results is a serious crime that has a direct impact on the integrity of the village head election process in Gampong Alue Ie Mirah, East Aceh. This article explores the practice of forgery, focusing on the village head election in the area, where several candidates allegedly used forged diplomas and invalid certificates of equivalency exam results. This research was conducted through a qualitative approach with a case study method, involving document analysis, interviews with related parties, and direct observation in the field. The results of the study show that this forgery not only violates criminal law, but also damages public trust in the village head election process, which should be carried out honestly and fairly. In addition, this article also discusses how law enforcement officers, both at the local and provincial levels, respond to and handle these forgery cases. The findings show that despite law enforcement efforts, challenges remain in terms of effective prevention and prosecution. The conclusion of this article emphasizes the importance of strengthening supervision and law enforcement to prevent similar cases from recurring in the future, as well as efforts to increase legal awareness among the public.